Spirituality, shifting identities and social change: cases from the Kalahari landscape - Lange, Mary E.; Dyll-Myklebust, Lauren (HTS Teologiese Studies / Theological Studies, 2015)
Storytelling, art and craft can be considered aesthetic expressions of identities. Kalahari identities are not fixed, but fluid. Research with present-day Kalahari People regarding their artistic expression and places where it has been, and is still, practised highlights that these expressions are informed by spirituality. This article explores this idea via two Kalahari case studies: Water Stories recorded in the Upington, Kakamas area, as well as research on a specific rock engraving site at Biesje Poort near Kakamas. The importance of the Kalahari People’s spiritual beliefs as reflected in these case studies and its significance regarding their identities and influence on social change and/or community development projects is discussed. The article thus highlights ways in which spirituality can be considered in relation to social change projects that are characterised by partnerships between local community, non-government and tertiary education representatives and researchers and that highlight storytelling as an integral part of people’s spirituality.
free
Keywords: Christianity and African religions; Colored people (South Africa); Folklore; African; Identity; Kalahari Desert; Petroglyphs; Serpents – Religious aspects; Spirituality; Storytelling; Water – Religious aspects